(untitled) - Barnett, Raymond A.; Raymond A. Barnett; Michael R. Ziegler; Karl E. Byleen (Upper Saddle River, N.J., 2000)
Written in a student-friendly format, this text prepares students to understand finite mathematics and calculus used in a wide range of disciplines. Covering relevant topics from finance, linear algebra, programming, and probability, the Seventh Edition places emphasis on computational skills, ideas, and problem solving. Other highlights include a rich variety of applications and integration of graphing calculators
Keywords: Mathematics